Paediatric Burn Fatalities: One Year Retrospective Study At Tertiary Care Center - Soni, Mahesh; Soral, Vikas; Verma, R K; Dutta, Sumanta (Journal of Forensic Medicine and Toxicology, 2026)
Introduction: Fire has fascinated humankind since ancient times and remains one of the most remarkable discoveries in human history. While it has significantly contributed to human evolution and progress, its misuse or mishandling can lead to catastrophic outcomes. Burn related incidents are mostly accidentals in children mostly due to there little develop ment of mind and body. These incidents often result in prolonged morbidity, permanent disability, or even death, causing profound loss to individuals, their families, society, and the state. Materials and Methods: This retrospective study was conducted in the Department of Forensic Medicine & Toxicology of a Tertiary care center. The study period spanned from 1st January 2024 to 31st December 2024. These cases were brought to the hospital mortuary for medico-legal postmortem examinations. Results: Total 4774 autopsies were conducted during this period. Out of these, 320 cases were have history of burn and 76 cases belong to paediatric population. The majority of the subjects in this study belonged to the toddler age group, fol lowed by those in early childhood. Male subjects outnumbered female subjects. Most of the cases were accidental burns. Preventive measures include educating caregivers, childproofing homes, promoting safe cooking practices, installing smoke alarms, advocating safety regulations, and providing first aid training. Strengthening paediatric burn care and researching risk factors are essential for effective interventions.